MONITORING THE CASH FLOWS OF THE RUSSIAN FEDERAL PENITENTIARY SERVICE (FSIN) - L. A. Malenkova (Финансы: теория и практика, 2017)
The results of the cash flow monitoring provide managers with the information basis for making sound management decisions in terms of improving the solvency, financial condition and effectiveness of the Federal Penitentiary Service. The paper discusses the key concepts of cash flows, a set of techniques and methods for their assessment and analysis, cash management objectives as well as the procedure for defining a net cash flow and ways to increase its management efficiency. To expand the number of persons involved in the formation of the company’s cash flow, the author proposes a scheme according to which structural units are assigned responsibility for the size of cash flows. The focus is put on the direct and indirect methods of making the cash flow statement for the study of factors relevant for the formation of positive, negative and net cash flows. There is a brief description of a methodology for determining the net cash flow from operating activities by an indirect method and the financial payment calendar in the tabular form. The cash flow budgeting procedure is shown as the essential element of the cash flow optimization. The importance of and the need for financial monitoring of cash flows with respect to the activities of the penitentiary system enterprises is emphasized.